Violence Against Healthcare Workers: Case Series - Cenger, Cüneyt Destan; Börtlüoğlu, Atiye; Tüzün, Birgül; Göktepe, Mustafa Cihad; Sezgin, Ayşen Ufuk; Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 2018)
The violence against health workers has been increasing worldwide and in Turkey, and is becoming a significant occupational health problem. The violence at healthcare settings is defined as “the threat behavior, verbal threat, economic abuse, physical aggression or sexual assault committed by the patient, patient’s relatives, or another individual, and causes risk for healthcare workers”. Our objective is evaluating the violence against healthcare workers who presented to outpatient clinics of Department of Forensic Medicine at … Five healthcare workers who presented due to the committed violence by the patient/patient’s relative were evaluated. The patients were aged between 26-47 years, and the mean age was 30.8 years. One patient was male. Three were physicians, one was a nurse, and the other was a caregiver. Physical violence in four patients, and psychiatric trauma in four patients were detected during the forensic examinations. Health workers have almost become the main responsible for the....
Keywords: violence; health services; forensic medicine